Kajian jarak antarbaris tebu dan jenis tanaman palawija dalam pertanaman tumpangsari = Study of sugarcane interrow space and secondary crop species in an intercropping - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
In sugarcane intercropping, intercrop was able to reduce the yield of sugarcane. The research aboutâ Study of sugarcane interrow space and secondary crop species in an intercroppingâ aimed to determine exact interrow space of sugarcane for each secondary crop species, that give the highest overall mixture crop yield and land equivalent ratio. A field experiment was conducted at Ngrancah Village, Pengasih Sub District, Kulon Progo District, 110 m above sea level with grumozol type. The treatment consisted of 2 factors arranged in a Split Plot Design with 3 replications.Three secondary crop species and 4 levels inerrow space of sugarcane were tested. The result showed that intercrops did not affect plant growth of sugarcane, but corn affected stalk weight and sucrose yield lower than peanut and soybean. Widening the interrow space from 100 cm to 110 cm was able to reduce stalk weight, sucrose yield, and overall mixture crops yield, but narrowing from 100 cm to 90 cm did not have significant effect. To change single interrow space from 100 cm to double interrow space (160+40) cm did not affect stalk weight and sucrose yield. Peanut and soybean in sugarcane interrow space 90, 100, and (160+40) cm showed overall mixture crops yield and land equivalent ratio higher than interrow space 110 cm.